2020
DOI: 10.1101/2020.08.31.20182428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beneficial Effect of Corticosteroids in Preventing Mortality in Patients Receiving Tocilizumab to Treat Severe COVID-19 Illness

Abstract: Introduction: On the basis of the preliminary report from the RECOVERY trial, the use of dexamethasone or alternative corticosteroids (CS) is currently recommended in severe COVID-19 patients requiring supplemental oxygen. However, last updated recommendations have not taken a position either for or against the use of other immunomodulators such as tocilizumab (TCZ), with or without CS, since results are still limited. Methods: From March 17 to April 7, 2020, a real-world observational retrospective analysis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…However, in line with the data of others, 7,10 we observed that IL-6 levels measured 24 h after an initial IV dose of TCZ increased significantly compared with pretreatment levels (Fig 1A ), presumably as a consequence of inhibiting uptake of the cytokine by its receptors. The increase in IL-6 was accompanied by an increase in D-dimers (Fig 1B ) and, in line with our previous data, 18 by an increase in plasma a-Def (Fig 1C).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…However, in line with the data of others, 7,10 we observed that IL-6 levels measured 24 h after an initial IV dose of TCZ increased significantly compared with pretreatment levels (Fig 1A ), presumably as a consequence of inhibiting uptake of the cytokine by its receptors. The increase in IL-6 was accompanied by an increase in D-dimers (Fig 1B ) and, in line with our previous data, 18 by an increase in plasma a-Def (Fig 1C).…”
Section: Resultssupporting
confidence: 92%
“…However, clinical trials with TCZ have not provided the expected benefits. 4,5 Indeed, an increase in D-dimers, a marker of fibrin turnover, has been recorded unexpectedly in TCZ-treated patients in some trials, [6][7][8][9][10] together with a trend to a higher death rate secondary to thromboembolism in one study. 11 Although it has been suggested that the protective effect reported of TCZ in some studies might be corticosteroiddependent, 12 other studies showed an increase in D-dimers in patients treated with TCZ whether or not corticosteroids were co-administered.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Excluding 1,157 nonpertinent titles or abstracts, the authors retrieved (in complete form) and assessed 11 studies according to the selection criteria (Fig 1). Six studies were further excluded because of the prespecified exclusion criteria: five because they were not randomized, [18][19][20][21][22] and one because it did not report outcomes of randomized patients. 23 The five RCTs finally included in the meta-analysis involved 7,692 patients (2,835 received corticosteroids and 4,837 received standard treatment 8,10-13 ; Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%